Through my eyes - Bridges, Ruby; Lundell, Margo (New York Scholastic, 1999)
Ruby Bridges recounts the story of her involvement, as a six-year-old, in the integration of her school in New Orleans in 1960
Hurg
5
Keywords: African American children -- Louisiana; African Americans -- Biography; New Orleans -- Race relations